Increasing the Absorption of Some Mineral Elements and the Quality of Apple Fruits by Foliar Spraying with Boron and Ascorbic Acid - Al-Dulaimi, Ali Suhail T.; Alrawi, Dheeaa Salih (Migration Letters, 2023)
A study was conducted in a 5-donum apple orchard, planted with 20-year-old Delicious Starking apple trees. The trees were spaced at a distance of 5x5 meters and were grafted onto seedling rootstocks (Borkh domestica Malus). The aim of the study was to investigate the effect of foliar spraying with boron and ascorbic acid on chlorophyll content, certain mineral elements, and fruit quality of the Delicious Starking apple variety, as well as to determine the compound that achieves the best results. The experiment was designed using a completely randomized design, consisting of four treatments and five replications per treatment, with one tree per replication. The treatments included: T0 (control): spraying with water only, T1: spraying with 170 ppm boron concentration, T2: spraying with 5.0 g/L ascorbic acid concentration, and T3: simultaneous spraying with 170 ppm boron concentration and 5.0 g/L ascorbic acid concentration. Results showed that foliar spraying with 170 ppm boron concentration and 5.0 g/L ascorbic acid concentration, either individually or in combination, enhanced the studied traits. The treatment combining boron and ascorbic acid provided the best results, as it significantly increased the chlorophyll content (2.60mg/g) compared to the control, as well as the potassium (0.56%), Phosphorus (0.22%), nitrogen (2.09%), and boron (19.4 ppm) levels. Additionally, it resulted in higher fruit weight and volume (172.9 g and 185.8 cm3, respectively) compared to the control (143.8 g and 155.6 cm3, respectively), and increased the total soluble solids and total sugars (13.51% and 16.15%, respectively). compared to the control (11.38% and 13.51%, respectively). In conclusion, foliar spraying with 170 ppm boron concentration and 5.0 g/L ascorbic acid concentration proved to be effective in improving the chlorophyll content, mineral elements, and fruit quality of the Delicious Starking apple variety. These findings highlight the potential of using these treatments as a means to enhance apple orchard management and maximize fruit quality